2019
DOI: 10.1101/517425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doublecotin-like kinase 1 increases chemoresistance of colorectal cancer cells through the anti-apoptosis pathway

Abstract: Colorectal cancer (CRC) is the third most common cancer diagnosed and the second leading cause of cancer-related deaths in the United States. About 50% of CRC patients relapsed after surgical resection and ultimately died of metastatic disease. Cancer stem cells (CSCs) are believed to be the primary reason for the recurrence of CRC. Specific stem cell marker, doublecortin-like kinase 1 (DCLK1) plays critical roles in initiating tumorigenesis, facilitating tumor progression, and promoting metastasis of CRC. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…However, the presence of tumor stem cells possessing chemoresistance, which accounts for approximately 0.05–0.1% of the total tumor cell mass, and harbor unlimited self-renewal competency, is the main cause of failure of cancer chemotherapy ( Zeuner et al, 2014 ). As a matter of fact, a great number of human kinases have been identified as coexistent putative markers of tumor stem cells, which contribute to minimizing 5-FU chemosensitivity in human cancers ( Li et al, 2019 ; Hou et al, 2020 ). In the current study, we observed the anti-CRC functions of 5-FU in a dose-dependent manner as expected, whereas the overexpression of STK35 in CRC cells partially reversed these effects, such as the promotion of apoptosis, tumor growth inhibition, and survival improvement in an in vivo mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of tumor stem cells possessing chemoresistance, which accounts for approximately 0.05–0.1% of the total tumor cell mass, and harbor unlimited self-renewal competency, is the main cause of failure of cancer chemotherapy ( Zeuner et al, 2014 ). As a matter of fact, a great number of human kinases have been identified as coexistent putative markers of tumor stem cells, which contribute to minimizing 5-FU chemosensitivity in human cancers ( Li et al, 2019 ; Hou et al, 2020 ). In the current study, we observed the anti-CRC functions of 5-FU in a dose-dependent manner as expected, whereas the overexpression of STK35 in CRC cells partially reversed these effects, such as the promotion of apoptosis, tumor growth inhibition, and survival improvement in an in vivo mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current chemotherapy does not possess the strength to fully eradicate solid tumors, resulting in secondary tumor and relapse. Owing to this, numerous efforts have been made to dissect the chemoresistant cancer cells based on the genes expressions, epigenetics, pathways signatures and therapeutic responses (Datta et al, 2016;Baharudin et al, 2017;Abu et al, 2019;Li et al, 2019). Although bulk transcriptomics is adequate to study the average gene expression signatures related to chemoresistance, they generally involve bulk tissue with assumption that all the cells obtained are of homogeneous material, thereby ignoring the stochasticity of gene expression (Raj and van Oudenaarden, 2008;Stegle et al, 2015).…”
Section: Possible Solution To Crc Chemoresistancementioning
confidence: 99%
“…Control of multiply critical biological pathways which are involved in the regulation of cell proliferation might be one of the critical underlying molecular mechanisms for DCLK1 to play its function during oncogenesis, progression, invasion and metastasis of CRC. Moreover, our previous findings also demonstrated that DCLK1 significantly increased the chemoresistance of CRC cells to 5-Fu treatment 26 . Therefore, DCLK1 can be developed as a novel therapeutic target for the treatment of colorectal cancer.…”
Section: Conclusion and Discussionmentioning
confidence: 64%